The impact of coal mining on the environment and community quality of life: a case study investigation of the impacts and conflicts associated with coal mining in the Mpumalanga Province, South Africa - Shongwe, Bonisile Nolwando (Department of Chemical Engineering, 2018)
Coal is South Africa's major primary energy source, and plays a significant role in supplying the chemicals and steelmaking industries. The benefits of coal production are relevant in the light of South Africa's development priorities of job creation and economic growth. Even so, primary metal production and coal-based power generation industries, through their operations and activities, pose a significant and irreversible risk to the surrounding environment. The impact on the environment further manifests on the health of local communities and on sustainable livelihoods, and frequently also presents a long-term economic burden and loss of valuable resources. Despite changes in legislation and improved social and environmental performance by the industry, there is growing concern over the impacts and conflicts associated with coal mining, with continuing claims by communities and civil society of associated health issues, cattle and livestock death, and destruction of livelihoods. However, to date, little attempt appears to have been made to support community concerns and perceptions with factual evidence and information, suggesting a lack of convergence between lay and expert knowledge. This dissertation investigates the facts, perceptions, concerns and conflicts in the mine-environment-community cause-effect chain in the context of the environmental and social impacts associated with the South African coal mining industry. More specifically this entails a detailed review of published data on academic literature, newspaper articles, popular magazines, and internet and specialist reports, with particular emphasis on the South African scenario; and semi-structured interviews with representatives from communities, civil society organisations, and independent environmental consultants. Particular focus is placed on coal mining in the Mpumalanga Province, which accounts for over 84% of South Africa's coal production. This was done with a view to developing a better understanding of the interrelationships between the coal mining industry and the local environment and society in which it operates. It is envisaged that this will ultimately serve to facilitate the development of sustainable solutions to the concerns and conflicts associated with coal mining. Historically, coal mining has had a significant impact on the environment and there is substantial evidence of a strong link between environmental pollution from mining activities and the health and well-being of humans and eco-systems in the surrounding vicinities. These impacts can be largely associated with water quality, physical and chemical land degradation, and air pollution through dust fall-out and emissions of particulate matter (PM) and toxic gases. In particular, AMD from coal mining results in significant pollution of land and water resources. The published literature provides evidence that this environmental pollution may, and often does, have an adverse effect on local eco-systems as well as on community health and livelihoods, particularly on crop and livestock farming. The findings also indicate that there has been response to these concerns by government and the industry. The government has instituted a number of legislative reforms, particularly since 2002, and has established programmes aimed at improving socio-economic challenges in mining towns. Industry has also taken steps to improve its environmental performance, in terms of waste management, mine water reclamation and post-closure rehabilitation. The literature findings were found to be largely consistent with the perceptions and concerns of communities, community support groups and consultants active in the coal-mining regions of Mpumalanga Province. The perceptions of the coal mining and processing sector were extremely negative; all participants expressed considerable concern over the environmental and social impacts. Emissions, particularly AMD and dust, from current and defunct workings and waste piles continue to be a source of water pollution, air pollution and land degradation which further have an adverse effect on aquatic life and human health as well as on livestock and crop productivity. Of particular concern in the coal-mining intensive area of Mpumalanga, is the impact of environmental pollution on maize production. With increasing public knowledge and awareness of these impacts, which can be largely attributed to the activities of the relatively large number of civil society organisations that now exist, the concerns and incidents relating to the environmental and socio-economic impacts from coal mining in the Mpumalanga area are generally well reported. The general consensus was that the concerns of communities and community-support organisations are not been taken seriously, and that government and industry are failing to alleviate the environmental degradation and human suffering in the Mpumalanga coal-mining areas. The lack of adequate response on the part of both the government and industry, and the continuing issues of environmental pollution and adverse community effects, have resulted in on-going (and possibly escalating) conflict situations in the form of community activisim, protests and litigation. This lack of response from government was, furthermore, considered as highly politicised and attributed largely to unethical arrangements between government officials and/or community leaders and mining corporations. Participants were generally of the perception that the negative aspects of coal mining outweigh any benefits and should be discontinued completely. The findings of this dissertation suggest that effective rehabilitation, consistent implementation and enforcement of the regulations designed to protect the environment and society, and stakeholder collaboration are a key requirement in terms of mitigating the environmental impacts and associated risks pertaining to human and livestock health and crop productivity. It is therefore recommended that the government address the rehabilitation of abandoned coal mines and discard dumps in the Mpumalanga Province, and establish action plans, linked to regional development plans, that are based on a comprehensive environmental monitoring programme in collaboration with other stakeholders, including communities, the mining industry and other business sectors in the region. A more detailed study on opportunities to improve the quality and availability of performance reporting by the coal industry is also recommended.